LEGAL ANALYSIS OF CRYPTO INVESTMENT IN ERA 4.0 VIEW FROM CREDO THEORY - Dedah Jubaedah; Hisam Ahyani; Haris Maiza Putra; Armelia Prakasa; Naeli Mutmainah (Diponegoro Law Review, 2022)
Today in the era of disruption 4.0, an interesting thing in Indonesia is related to the presence of Crypto Investments such as Bitcoin (digital currency), where which is one of the economic indicators that can affect the global economy. Now business transactions are using online media (digitalization). Therefore, the Indonesian people need legal certainty in utilizing transactions for this crypto investment activity. This study aims to legally analyze crypto investments used for buying and selling transactions in Indonesia from the perspective of Islamic law and creed theory. This study uses the Library Research Method, where the data is obtained by means of a literature study through laws, government regulations, Fatwa DSN MUI, and the theory of creed / testimony / Shahadah. As a result, by referring to the creed theory that Crypto Investments such as Bitcoin have laws that are permitted when used as a medium of exchange. This law only applies to parties who acknowledge and are willing to use it. Meanwhile, Bitcoin as an investment is illegal. However, Crypto as a transaction tool in online trade is a renewable innovation in economic development in Indonesia today. So there is a need for special regulations to use Crypto.